2019
DOI: 10.1039/c9tb00310j
|View full text |Cite
|
Sign up to set email alerts
|

A red lysosome-targeted fluorescent probe for carboxylesterase detection and bioimaging

Abstract: A red lysosome-targeting probe for carboxylesterase activity has been successfully applied in complex biological samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 52 publications
1
27
0
1
Order By: Relevance
“…In 2019, Zhou's group reported a red emission lysosome‐targeted probe 6 . It is a fluorescence “off‐on” probe with the ability to selectively and sensitively detect carboxylesterase in living cells, sera as well as tissues (Figure e).…”
Section: Classification and Functions Of Cessmentioning
confidence: 99%
“…In 2019, Zhou's group reported a red emission lysosome‐targeted probe 6 . It is a fluorescence “off‐on” probe with the ability to selectively and sensitively detect carboxylesterase in living cells, sera as well as tissues (Figure e).…”
Section: Classification and Functions Of Cessmentioning
confidence: 99%
“…Nanoprobes, as novel kinds of contrast agents, have been extensively used in medical imaging and drug delivery given their size and optical properties, which translate to high resolution, sensitivity and other advantages 4 - 8 . The nanoprobes with imaging abilities are especially suitable for real-time imaging, which could greatly improve the accuracy of early tumor diagnosis and therapeutic monitoring 9 , 10 . In fact, several nanoprobes have been designed in recent years for the early diagnosis and monitoring of tumors 11 .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] For example, Zhou et al reported a new lysosome-targeted uorescence probe with emission 575 nm for uorescence sensing of carboxylesterase in live cells, sera and tissues. 27 As for in vivo imaging studies, near-infrared (NIR) uorescent probes are more desired because they have excellent tissue penetration, low biological and autouorescence damage. [28][29][30][31][32] As far as we know, most of the current probes have a severe limitation on application for imaging in living systems, since they have a short excitation (usually <500 nm) and emission wavelength (usually <630 nm) and there are limited reports on NIR uorescent probes for carboxylesterase detection in recent years.…”
Section: Introductionmentioning
confidence: 99%